2018
DOI: 10.1063/1.5005870
|View full text |Cite
|
Sign up to set email alerts
|

A non-Fourier approach towards the analysis of heat transfer enhancement with water based nanofluids through a channel

Abstract: In this article, a non-Fourier approach to model the heat transfer phenomenon in nanofluids having application to automotive industry is studied. In this respect, a recently proposed hyperbolic heat flux equation is embedded into the heat energy equation and thereby incorporating the effect of thermal relaxation time. Nanofluids are formed by considering copper oxide (CuO), Titanium dioxide (TiO2) and Aluminum oxide (Al2O3) nano-solid particles in the base fluid. The flow governing system of PDEs along with bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Pr represents the Prandtl number, signifying the ratio of momentum to thermal diffusivity, and λ is the dimensionless relaxation time. The physical parameters referenced in Equation (10) are defined in the nomenclature. By solving Equations ( 5)-( 8) while considering the boundary conditions (9) and utilizing the method of variation of parameters, the study yields the following solutions:…”
Section: Solution Of the Flow Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Pr represents the Prandtl number, signifying the ratio of momentum to thermal diffusivity, and λ is the dimensionless relaxation time. The physical parameters referenced in Equation (10) are defined in the nomenclature. By solving Equations ( 5)-( 8) while considering the boundary conditions (9) and utilizing the method of variation of parameters, the study yields the following solutions:…”
Section: Solution Of the Flow Modelmentioning
confidence: 99%
“…They observed that relaxation time and dimensionless time influenced the location of temperature discontinuities, while porosity and frequency had no impact on temperature discontinuities. A non‐Fourier approach to model the heat transfer phenomenon in nanofluids with application to the automotive industry is studied by Dil and Khan, 10 where they concluded that the new approach is more general and thus allows predicting the influence of thermal relaxation time on the heat transfer characteristics. Caltagirone 11 examined non‐Fourier heat transfer at small scales of time and space.…”
Section: Introductionmentioning
confidence: 99%
“…Systems such as technical equipment and natural phenomena such as the movement of temperature stratifed masses of air and water on Earth exhibit mixed convection fow [2,3]. It has uses in heat exchangers [4], thermal design, cooling electronic components, and other felds. It is also pertinent to heat transfer and fuid fow analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the numerous applications in radiative therapy, metal casting technology, and ceramic engineering, several studies [4,19] have explored the infuence of radiative efect at the boundary layer with the transfer of heat characteristics. In biomedical engineering, within the context of blood fow [20,21], the Casson parameter has been considered in analyzing the behavior of non-Newtonian fow in arteries [22][23][24].…”
Section: Introductionmentioning
confidence: 99%